Diatomáceas epífitas e físico-químico da água como instrumento de avaliação da qualidade ambiental de lagos tropicais - Oliveira, Adriana Lacerda de (2014)
The present study aimed to characterize the Nymphoides indica (L.) Kuntze epiphytic diatoms in Cauamé Campus and Trevo lakes, both of savannah lakes in Boa Vista/RR, in the months of May, July, September and November 2012. Epiphytic diatom samples were taken at two points in each lake, and the material was oxidized and subsequently prepared permanent slides. Simultaneously, the col-lections of N. indica, determine the pH, water temperature, and also made the collec-tion of water for analyzes of nutrients (ammonium ion, nitrate, nitrite, phosphate and silica) and dissolved oxygen. In both lakes surveyed, there was 75 diatom species, grouped in 19 genera and 14 families, 25 species identified only in Cauamé Campus lake. In Trevo lake record only 34 species. Of these, 09 species in the Cauamé Campus lake and 18 species in the Trevo lake were described pioneered for the Roraima’s state . The most representative families are Eunotiaceae and Pinnulariaceae. Eunotia and Pinnularia constitute the most significant genres, with 25 and 11 taxa, respectively. Thus, through these aspects, which are consistent with the identification of pH and nutrients, we found that the water of Cauamé Campus and Trevo lakes are tropical, oligotrophic, acidic and unpolluted.